The pig war : how a porcine tragedy taught England and America to share - Smith, Emma Bland (Calkins Creek, an imprint of Boyds Mills & Kane, 2020)
In 1859, the British and Americans coexist on the small island of San Juan, located off the coast of the Pacific Northwest. They are on fairly good terms--until one fateful morning when an innocent hog owned by a British man has the misfortune to eat some potatoes on an American farmer's land. In a moment of rash anger, Lyman Cutlar shoots Charles Griffin's pig, inadvertently almost bringing the two nations to war. Tensions flare, armies gather, cannons are rolled out... all because of a pig! Emma Bland Smith's humorous text and Alison Jay's folksy illustrations combine in this whimsical nonfiction picture book that models the principles of peaceful conflict resolution.